(untitled) (Journal of Scientific Research, 2025)
Basalt preserve palaeomagnetic record, essential for the correlation of the lava flows which is important to establish flow stratigraphic sequence. The present study encompasses, palaeomagnetic polarity of the Deccan basalt lava flows, exposed in Chhatri Talao hill (part of Pohra hill ranges), due east of Amravati city, Maharashtra State, India. During the present study, flow mapping was carried out with collection of basalt rock samples for palaeomagnetic investigation. Geological field results indicate exposure of three basalt lava flows between altitude of 365 to 435 meter (amsl), which are (i) lower flow-I: fine to medium grained, mafic plagioclase microphyric basalt; (ii) middle flow-II: coarse grained, mafic plagioclase phyric basalt and (iii) upper flow-III: fine to medium grained, mafic plagioclase microphyric basalt. Results also indicate, ‘Normal’ polarity of upper two lava flows (flow-II and flow-III), exposed at an altitude of 427-440 meter and 398-427 meter (amsl), and ‘Reverse’ palaeomagnetic polarity by the lower flow (flow-I) at an altitude of 380-398 meter (amsl). Thus, present study, can be useful to correlate eastern basalt lava flows with other parts of the Deccan basaltic terrain. This study can be useful to determine the palaeo-latitudes of eastern Deccan basalt lava flows.